Coupling Relationship of Human Activity and Geographical Environment in Stage-Specific Development of Urban Coastal Zone: A Case Study of Quanzhou Bay, China (1954–2020) - Xiao, Xianbiao; Li, Yunhai; Shu, Fangfang; Wang, Liang; He, Jia; Zou, Xiaochun; Chi, Wenqi; Lin, Yuting; Zheng, Binxin (Frontiers in Marine Science, 2022)
Owing to the development of the social economy, the geographical environment and ocean utilization patterns of urban coastal zones have changed. This change, in turn, has influenced the socio-economic development of urban coastal zones. Based on the Geographic Information System technology, the area, coastline length, and shoreland use function of reclamation areas were obtained from the geographic charts (1954–2020) and remote sensing data (1988–2017) of Quanzhou Bay. In this study, we analyzed the geomorphologic change process and the relationship between land use patterns and economic development in Quanzhou Bay from the perspectives of hydrodynamics, sediments, and human activity. Our results indicated that over the past 70 years, the bay area has reduced by 21.5%. The length of the coastline decreased from 208.36 km in 1959 to 149.11 km in 1988, whereas the shape index of the bay (SIB) decreased from 3.09 to 2.41 during the same period. Between 1988 and 2017, the coastline increased to 162.91 km, causing the SIB to increase to 2.72. The artificial index of the bay increased from 0.28 in 1959 to 0.90 in 2017. The intensity of bay the development (IBD) first increased from 0.27 in 1959 to 0.77 in 2006. During the transition to a more modern society (2006 to present), the IBD slightly decreased to 0.73 in 2017. Affected by human activity, the transformation of the reclaimed land in Quanzhou Bay can be divided into four stages that are closely linked to the economic development in the region. In the early industrialization period, reclaimed land in the region was used for agricultural production, whereas in the mid-industrialization period, it was gradually transformed into a combination of industrial (29.8%) and agricultural (56.1%) lands. In the later period of industrialization, the reclaimed land was gradually converted into urban industrial and port lands. Finally, with further refinement and upgrading of economic and industrial structures, the socio-economic and environmental benefits from coastal reclamation projects have been increasing, whereas the proportion of economic benefits (in the total benefits) has been decreasing. The results of this study can provide decision-making references for the optimization of utilization patterns and the economic development of reclamation lands in coastal areas.